Big data for (not so) small loans: Technological infrastructures and the massification of fringe finance - Langevin, Marie (Review of International Political Economy, 2019)
This article examines the evolution of the sociotechnical systems that is leading to a massive increase in the overall indebtedness of marginalized populations in the Global South. I analyze the processes through which Big Data (or alternative data) technologies are transforming the infrastructure of fringe finance, the nature of its power relations, and its capacities. The article identifies the consequences of these technological transformations on financial practices and illustrates the qualitative nature of the changes involved. I propose that while these innovations have increased the power of this market to capture value, they have also increased risks to indebted populations and the infrastructure's stability. I argue that these financial practices, enhanced by the power of Big Data, have made the infrastructure of fringe finance dangerously hermetic to careful consideration of the productive capacities of those being targeted for inclusion into the formal financial system, thereby making it potentially dysfunctional.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; discipline; inclusion financière; périodes historiques; ressource en ligne; sciences de la gestion; économie